2011
DOI: 10.1017/s1461145711001003
|View full text |Cite
|
Sign up to set email alerts
|

Lamotrigine blocks NMDA receptor-initiated arachidonic acid signalling in rat brain: implications for its efficacy in bipolar disorder

Abstract: An upregulated brain arachidonic acid (AA) cascade and a hyperglutamatergic state characterize bipolar disorder (BD). Lamotrigine (LTG), a mood stabilizer approved for treating BD, is reported to interfere with glutamatergic neurotransmission involving N-methyl-D-aspartate receptors (NMDARs). NMDARs allow extracellular calcium into the cell, thereby stimulating calcium-dependent cytosolic phospholipase A2 (cPLA2) to release arachidonic acid (AA) from membrane phospholipid. We hypothesized that LTG, like other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 89 publications
2
22
0
Order By: Relevance
“…A similar reduction in plasma unesterified fatty acids has been found with other mood stabilizers and antipsychotics used to treat BD, such as lamotrigine, olanzapine and clozapine (Ramadan et al, 2011; Cheon et al, unpublished observation) suggesting a common peripheral effect of these drugs. The decrease in plasma unesterified fatty acids may be due to (i) reduced liver secretion of lipoprotein-bound esterified fatty acids, the main source of unesterified fatty acids in plasma, or (ii) reduced release of unesterified fatty acids from adipose tissue by lipases.…”
Section: Discussionsupporting
confidence: 58%
“…A similar reduction in plasma unesterified fatty acids has been found with other mood stabilizers and antipsychotics used to treat BD, such as lamotrigine, olanzapine and clozapine (Ramadan et al, 2011; Cheon et al, unpublished observation) suggesting a common peripheral effect of these drugs. The decrease in plasma unesterified fatty acids may be due to (i) reduced liver secretion of lipoprotein-bound esterified fatty acids, the main source of unesterified fatty acids in plasma, or (ii) reduced release of unesterified fatty acids from adipose tissue by lipases.…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, the endogenous concentration observed in this experiment was almost equivalent to the values in other reports. 35 Taken together, this study demonstrated the feasibility of this method for sample preparation and quantitation.…”
Section: Quantitative Validationsupporting
confidence: 54%
“…Surprisingly, only a small number of experiments reported the interaction of lamotrigine with NMDA receptors. For instance, a novel study reported that lamotrigine is effective in treatment of bipolar disorder through blockade of NMDA receptors [66]. Although the blockade of neuronal voltage-dependent sodium (n = 8).…”
Section: Discussionmentioning
confidence: 99%